An Overview of the Strategic Advantages of AI-Powered Threat Intelligence in the Cloud - Mallikarjunaradhya, Vinay; Pothukuchi, Ameya Shastri; Kota, Lakshmi Vasuda (Journal of Science & Technology, 2023)
Cloud adoption has become synonymous with business agility and scalability in the digital transformation era. However, this shift has also ushered in a new wave of security threats, necessitating advanced protective measures. Artificial Intelligence (AI) has emerged as a beacon of hope, promising adaptive, predictive, and automated security solutions. Cloud security is becoming more critical than ever with a rise in cyberattacks. AI can improve cloud security drastically. This study examines AI’s significant influence on cloud security, challenges, and opportunities from the vantage point of product leaders. Through a comprehensive exploration of market dynamics, product development nuances, and strategic considerations, this paper offers insights into the pivotal role of product managers in shaping the future of cloud security.
Keywords: Artificial Intelligence; Cloud computing; Cyber Security; Microsoft Azure; Predictive Analytics; Software-as-a-Service; SAAS